Analysis of diagnosis and treatment of complicated cervical severe adhesion atresia after removal of endometrial stromal nodule: A case report. Issue 48 (December 2017) - Zhang, Rui; Gu, Pei; Liu, Qi; Li, Bin; Bai, Wenpei
Abstract: Rationale: Endometrial stromal nodule (ESN) is a rare benign endometrial stroma tumor.Experiences are helpful for avoiding and treating similar postoperative complications (cervical adhesions and atresia). Patient concerns: When appearing in the cervical, this tumor can easily lead to complications after the surgical resection. The diagnosis and postsurgery complication of a young woman's ESN was reported here. Diagnoses: The postoperative pathological diagnosis was ESN. Interventions: A 29-year-old young woman was diagnosed and treated for ESN in cervical parts with postsurgery complications of cervical complex adhesion atresia. Outcomes: The complication was complex cervix adhesion atresia with very special imaging performance—the cervix and the palace imaged as "Twisted and Angled Staircase." This particular cervix adhesion was challenging for operation. We achieved a successful treatment through the carefully designed surgical procedure including the application of hysteroscopy and laparoscopy. Lessons: The lower uterine segment and cervix should be paid attention during suturing in this situation. Close and positive follow-ups should be planned after the endometrial stromal resection. The reconstruction of the tunnel is a solution for the problem of menstruation.